Reproducing Rights: How New Technologies Challenge the Legal Foundations of Genetic Relatedness and Human Dignity - Fatima, Anza; Amjad, Balqees; Jibran, Muzammil; Ahmad, Jalil (ACADEMIA International Journal for Social Sciences, 2025)
The use of assisted reproductive technologies (ARTs) is the realization of a universally desired future is the ability to create and raise a genetically related child if needed. For some, existing assisted reproductive technology won't help, but upcoming techniques such as in vitro derived gametes (IVGs) may. Yet the desire to have genetically related children is often criticized in discussions about new assisted reproductive technology. This is especially true because most heterosexual couples can have such children without help, while same-sex couples want them as well. This paper presents the moral and legal reasons why IVGs should be legalized when deemed safe enough. This paper analyzes the development of the concept of "treatment" in the relevant laws of the United Kingdom and argues that it is reasonable to attach importance to reproductive parenting programs, thus refuting the "There is a moral obligation to adopt" or "Adoption or donor fertilization should be sufficient" argument. The law of fertility in the social life of the general status of recognition and the right to private and family life, and the right not to be discriminated against, in particular under the European Convention on Human Rights, was discussed, with emphasis on the disabling nature of infertility.